Catanionic Coacervate Droplets as a Surfactant‐Based Membrane‐Free Protocell Model. (2nd October 2017) - Douliez, Jean‐Paul; Martin, Nicolas; Gaillard, Cédric; Beneyton, Thomas; Baret, Jean‐Christophe; Mann, Stephen; Beven, Laure
Abstract: We report on the formation of surfactant‐based complex catanionic coacervate droplets in mixtures of decanoic acid and cetylpyridinium chloride or cetyltrimethylammonium bromide. We show that coacervation occurs over a broad range of composition, pH, and ionic strength. The catanionic coacervates consist of elongated micelles, sequester a wide range of solutes including water‐soluble organic dyes, polysaccharides, proteins, enzymes, and DNA, and can be structurally stabilized by sodium alginate or gelatin‐based hydrogelation. These results suggest that catanionic coacervates could be exploited as a novel surfactant‐based membrane‐free protocell model.